Learning assessment in the school context: Brief analysis (historical context, objectives and challenges) (Research, Society and Development, 2022)
Learning or school assessment is a complex process that requires, for its conceptual understanding, a brief analysis of its historical context. In the current Brazilian educational process, the discussion about the true objectives of evaluation unfolds in challenges for national education, for schools, for students and educators. The present study is justified by the need to alert education professionals about the true understanding of the real objective of evaluation and its importance not only in the process of learning and training of students but in favor of improvements in teaching methodology and didactics and aims to sensitize teachers and pedagogues about the need to promote urgent changes in the evaluation process in basic education, analyzing the historical context of evaluation and discussing its objectives and challenges. To this end, the methodological procedure used in this research was an exploratory bibliographic research. Data collection and analysis was carried out in a virtual environment, in reliable databases and in articles published on scientific articles websites and renowned institutions, as well as in books. The results and discussions were presented in two different topics, namely: School evaluation, brief historical context; School evaluation, between objectives and current challenges. And the author's conclusions and impressions in the final considerations.